The European Union, the United States, and Trade: Metaphorical Climate Change, Not Bad Weather - Schwartz, Herman Mark (2022)
US and EU trade relations exhibit a set of chronic and secularly unsustainable imbalances, in which new Schumpeterian leading sectors and catch-up growth create growing tension in the asymmetrical and somewhat hierarchical US–EU relationship. These imbalances exhibit two distinct cycles interrupted by a clear structural break in the 1970s and an emerging cycle after the 2008–2010 crises. Each cycle has seen rising US current account or trade deficits with Europe provoke some financial or political crisis. Each crisis produced a US-led solution producing even greater imbalances in the next cycle, with concomitant stress on the asymmetric US–EU relationship. The EU and particularly the northern eurozone economies typically have relied on export surpluses for growth. But relying on export surpluses for growth reinforces EU dependence on the US and the US dollar at a time when US domestic politics are increasingly hostile to trade deficits and tension with China is rising.